Pengaruh Penerapan Akuntansi Pertanggungjawaban Terhadap Pengendalian Biaya Pada CV. Perdamaian - Hafizah Lutfiyyah Nur jihan; Tiara, Shita (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2024)
The research results show that Organizational Structure has a positive effect on Cost Control at CV. Perdamaian Medan. This can be seen from the value of tcount (4.144) > ttable (1.68385) with a significant value (0.000<0.05), Budget Planning has a positive effect on Cost Control at CV. Perdamaian Medan. This can be seen from the value of tcount (2.332) > ttable (1.68385) with a significant value (0.025 < 0.05) and reporting has a positive effect on Cost Control at CV. Perdamaian Medan. This can be seen from the value of tcount (1.865) > ttable (1.68385) with a significant value (0.032<0.05). Organizational Structure, Budget Planning and Reporting simultaneously have a positive effect on Cost Control at CV. Perdamaian Medan. This can be seen from the value of tcount (3.238) > ttable (1.68385) with a significant value (0.000 < 0.05).